2014
DOI: 10.1111/cen.12454
|View full text |Cite
|
Sign up to set email alerts
|

Procollagen type I N‐terminal peptide in preterm infants is associated with growth during the first six months post‐term

Abstract: Increased growth in SGA compared with AGA preterm infants is reflected by increased collagen type I synthesis during the first six months post-term, suggesting that PINP and UHP correspond with growth in preterm infants. An explanation for decreased bone acquisition of SGA preterm infants may be that increased collagen type I synthesis is not directly followed by increased bone mineralization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“… 27 Only 6 SGA infants (1.3%) were included out of 456 eligible participants in our study, while neonatal bone turnover in SGA cases may differ from bone metabolism in AGA subjects. 28 Nevertheless, no previous studies have investigated both TRACP-5b and NTx simultaneously in the context of vitamin D deficiency during early infancy, making our studies significant.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Only 6 SGA infants (1.3%) were included out of 456 eligible participants in our study, while neonatal bone turnover in SGA cases may differ from bone metabolism in AGA subjects. 28 Nevertheless, no previous studies have investigated both TRACP-5b and NTx simultaneously in the context of vitamin D deficiency during early infancy, making our studies significant.…”
Section: Discussionmentioning
confidence: 99%
“…There are planty of studies concerning bone mineralization in children born small for gestational age (SGA). Van de Lagemaat showed that six months post-term SGA preterms have lower bone accretion and in another work she proved decreased collagen type I synthesis in SGA children [2,3]. Longhi also confirmed that children born as SGA seem to have smaller and weaker bones [4].…”
Section: Introductionmentioning
confidence: 89%
“…OC also plays an important role in energy metabolism as a bone-derived hormone. Bone resorption markers mainly comprise collagen type I degradation products: cross-linked N- and C-telopeptides (NTx and CTx) [10, 11]. Additionally, C-type natriuretic peptide plays an essential role in bone and cartilage growth, while its stable product, amino-terminal propeptide of C-type natriuretic peptide (NT-proCNP), serves as a growth plate activity marker [12].…”
Section: Introductionmentioning
confidence: 99%